2020
DOI: 10.1016/j.cca.2020.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Elecsys® Anti-SARS-CoV-2 immunoassay with the EDI™ enzyme linked immunosorbent assays for the detection of SARS-CoV-2 antibodies in human plasma

Abstract: Background: Here, we report on a head-to-head comparison of the fully-automated Elecsys® Anti-SARS-CoV-2 immunoassay with the EDI TM enzyme linked immunosorbent assays (ELISA) for the detection of SARS-CoV-2 antibodies in human plasma. Methods: SARS-CoV-2 antibodies were measured with the Elecsys® assay and the EDI TM ELISAs (IgM and IgG) in 64 SARS-CoV-2 RT-PCR confirmed COVID-19 patients with serial blood samples (n = 104) collected at different time points from symptom onset. Blood samples from 200 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 9 publications
10
126
2
1
Order By: Relevance
“…7 Additionally, Egger et al similarly revealed the high sensitivity (100%) and specificity (false positivity <1) of the Elecsys Anti-SARS-CoV-2 test using plasma samples. 6 Although rigorous differences between the results of the Elecsys Anti-SARS-CoV-2 assay using serum and plasma might not be sufficiently clarified in the manufacturer's instructions (of Elecsys Anti-SARS-CoV-2), both samples could be utilized for the test (https://diagnostics.roche. com/jp/ja/products/params/elecsys-anti-sars-cov-2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Additionally, Egger et al similarly revealed the high sensitivity (100%) and specificity (false positivity <1) of the Elecsys Anti-SARS-CoV-2 test using plasma samples. 6 Although rigorous differences between the results of the Elecsys Anti-SARS-CoV-2 assay using serum and plasma might not be sufficiently clarified in the manufacturer's instructions (of Elecsys Anti-SARS-CoV-2), both samples could be utilized for the test (https://diagnostics.roche. com/jp/ja/products/params/elecsys-anti-sars-cov-2.…”
Section: Discussionmentioning
confidence: 99%
“…html#north-america). Thus, although this point should be considered during interpretation, considering our results and recent reports, 6,7 we mainly focused on the evaluation of the time-dependent change in the seroprevalence of outpatients with liver disease, who were asymptomatic for COVID-19, by the results of the Elecsys Anti-SARS-CoV-2 immunoassay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2-IgG were detected second to third weeks after onset of symptoms in up to 100% of hospitalized patients by use of various commercial immunoassays [ 2 ], [ 7 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ]. It has been shown that SARS-CoV-2-IgG titers were higher in critical cases compared to less critical patients and that severe ill patients seroconverted earlier than mild cases [ 7 ], [ 13 ], [ 14 ].…”
Section: Introductionmentioning
confidence: 99%